MENGGAGAS ETIKA BERKOMUNIKASI DIGITAL: PROGRAM SOSIALISASI PADA REMAJA KELAS 7 DI SMP PUTRA BANGSA DEPOK - Nataly, Febriansyah; Setyadji, Veronika; Purnamasari, Yuli; Alfian, Alfian; Sabrina, Afiyah; Alifah, Hasna Nismara; Natalia Zai, Ika Nuraini; Haikal Fadillah, Muhammad; Nindita, Nazwa Ayu; Akbar, Rizki Buli; Deviani, Syavalia (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
Negative effects of social media use may include the emergence of consumerist tendencies and hedonism. Lack of knowledge regarding communication ethics on social media causes a lack of awareness of the importance of policies in social media. Several teachers also said that many Putra Bangsa Middle School students experienced complaints about using social media, such as receiving negative comments and not understanding how to respond to issues or content on social media. The aim of carrying out this service activity is to educate about the importance of communication ethics on social media. This research has important implications in shaping student character in the digital era. Increasing understanding of communication ethics can help students interact positively and responsibly on social media platforms. The hope of this research is that Putra Bangsa Middle School students can participate actively in implementing communication ethics in social media. In this way, it is hoped that they can become critical and responsible individuals in communicating not only in the real world but also in cyberspace. In conclusion, this counseling has a positive impact in shaping student character and reflects concern for the formation of a generation with character in Indonesia.